Settling velocity variation induced by a sphere moving across a two-layer stratified fluid with different rheological characteristics. Issue 14 (27th March 2023) - Pan, Jinghan; Tu, Chengxu; Kan, Mengwen; Shan, Jiaming; Bao, Fubing; Lin, Jianzhong
Abstract : Particle settling in stratified fluids is widespread in chemical and pharmaceutical processes, and how to effectively regulate the particle velocity is the key to optimizing the above process technology. Abstract : Particle settling in stratified fluids is widespread in chemical and pharmaceutical processes, and how to effectively regulate the particle velocity is the key to optimizing the above process technology. In this study, the settling of individual particle in two stratified fluids, water–oil and water–PAAm was studied using the high-speed shadow imaging method. In the Newtonian stratified fluid of water–oil, the particle penetrates the liquid–liquid interface and forms unsteady entrained drops of different shapes, and the settling velocity becomes smaller. In contrast, in water–PAAm stratified fluids, the shear-thinning and viscoelasticity of the lower fluid will cause the entrained drops of the particle to appear a stable sharp cone shape, and the particle can thus obtain a smaller drag coefficient ( < 1) and a significantly enhanced settling velocity ( U * > 1) compared to the uncovered PAAm solution (PAAm solution without overlayer oil). This study can provide a new path for the development of new particle velocity regulation techniques.